Frontispiece: Two‐Dimensional Photosensitizer Nanosheets via Low‐Energy Electron Beam Induced Cross‐Linking of Self‐Assembled RuII Polypyridine Monolayers. Issue 28 (4th July 2022) - Küllmer, Maria; Herrmann‐Westendorf, Felix; Endres, Patrick; Götz, Stefan; Reza Rasouli, Hamid; Najafidehaghani, Emad; Neumann, Christof; Gläßner, Rebecka; Kaiser, David; Weimann, Thomas; Winter, Andreas; Schubert, Ulrich S.; et al.
Abstract : Nanomembranes . In their Communication (e202204953 ), Andrey Turchanin et al. present two concepts to introduce a photoactive Ru(II) polypyridine complex into carbon nanomembranes. The photoactive units are either directly incorporated into the scaffold or covalently grafted to its surface. Frontispiece art by Ilia Ghiasedin.